Cognitive and emotional outcomes after prolonged education: a quasi-experiment on 320 182 Swedish boys. (2nd June 2016) - Lager, Anton; Seblova, Dominika; Falkstedt, Daniel; Lövdén, Martin
Abstract: Background: Cognitive and socio-emotional abilities are powerful predictors of death and disease as well as of social and economic outcomes. Education is societies' main way of promoting these abilities, ideally so that inequalities by socioeconomic background are reduced. However, the extent to which education serves these cognitive, social-emotional and equality objectives is relatively unknown and intensively debated. Drawing on a Swedish school reform that was explicitly designed as a massive quasi-experiment, we assessed differential impact of education on intelligence and emotional control across childhood socioeconomic position. We also assessed initial differences in abilities by childhood socioeconomic position and how well childhood socioeconomic position and abilities predict all-cause mortality. Methods: The Swedish comprehensive school reform, rolled out during the 1950s, extended compulsory education from 8 to 9 years in some municipalities whereas others were kept as controls for the sake of evaluation. We followed eight full cohorts of Swedish boys born between 1951 and 1958, who lived in 1017 municipalities with known experimental status (344 336 boys) and whose childhood socioeconomic position was known (320 182 boys). At conscription, intelligence was measured by four subtests and emotional control (calm and efficient responses in various situations) was rated by a military psychologist. Both measures were standardized to have a mean of 100 and standard deviation of 15. All-cause mortality was recorded until 49–56 years of age. Results: The reform had an average positive impact on intelligence of 0.75 IQ units (95% confidence interval (CI): 0.54, 0.97; P < 0.0005). The impact on emotional control was negative; −0.50 units (95% CI: −0.72, −0.28; P < 0.0005). Both effects differed by socioeconomic background so that the average IQ difference between sons of high non-manual and unqualified manual workers was reduced from 16.32 to 15.57 units and the difference in emotional control was reduced from 6.50 to 5.63 units. All-cause mortality was predicted by low childhood socioeconomic position [hazard ratio (HR) = 1.15 [95% CI: 1.11, 1.20], P < 0.0005], low intelligence [HR = 1.39 (95% CI: 1.34, 1.44), P < 0.0005] as well as low emotional control [HR = 1.61 (95% CI: 1.55, 1.67), P < 0.0005] in mutually adjusted models. Conclusions: Extending compulsory education promoted intelligence but lowered emotional control, and reduced disparities over social background in both. Emotional control was the strongest predictor of all-cause mortality. Our results are in line with the idea that education is important in our efforts to achieve healthy, competent and fair societies, but much more work is needed to understand the links between education and non-cognitive skills.